Formulate a Marketing Strategy for a Newly Established Accountancy Business - Smith, Sarah Louise (2007)
Ridge & Smith Associates Limited (R&S) are a newly established firm of Chartered Management Accountants based within the East Midlands. The purpose of this report is to formulate a Marketing Strategy that R&S can adopt within their business.